Metacognitive thinking skills as indicators of mental health: Possible effects of alexithymia levels - Tolba, Engy; Rabbo, Ali Abd (Edelweiss Applied Science and Technology, 2025)
This study aimed to examine the potential effects of alexithymia levels on metacognitive thinking skills among university students by identifying the prevalence levels of alexithymia, determining the level of metacognitive thinking skills, and examining the effects of alexithymia levels on metacognitive thinking skills that are indicators of mental health. A descriptive and comparative research design was adopted to analyze behavioral patterns related to alexithymia and metacognition. The sample included 120 male and female university students randomly selected from the population. The Toronto Alexithymia Scale and the Metacognitive Thinking Scale were administered to measure the main variables. The results revealed that students exhibited generally high levels of both alexithymia and metacognitive thinking. However, significant differences were observed among groups; students with low alexithymia levels demonstrated superior metacognitive thinking skills compared to those with medium and high levels. These findings highlight the inverse relationship between alexithymia and metacognitive capacity and that alexithymia affects metacognitive thinking skills, which are important indicators of a learner's mental health. Alexithymia negatively affects students’ ability to monitor, evaluate, and regulate their own cognitive processes, which may have implications for their overall mental health and academic performance. The study recommends implementing psychoeducational programs that enhance emotional awareness, imaginative engagement, and reflective practices to strengthen metacognitive thinking and support students’ psychological well-being.